Revisional Study of the Order Palaeodictyoptera in the Upper Carboniferous Shales of Commentry, France Part II (Psyche: A Journal of Entomology)
An introductory discussion of the Palaeodictyoptera found in the Commentry shales and of the coIlection in the Institut de Paléontologie in Paris, as well as an account of the background of this investigation, was included in the first part of these studies. The present part deals with the following seven families: Homoiopteridae, Lycocercidae, Graphiptilidae, Breyeriidae, Eugereonidae, Archaemego-aptilidae and Megaptilidae. Compared with the Spilapteridae, considered in Part I, all of these families are small, consisting of only a few genera, at least from the Commentry shales. However, they show much diversity of structure and indicate the extensive range of wing modifications which occurred in the Palaeodictyoptera, including the reduction and shortening of the hind wings. The third part of this study will deal with the Dictyoneuridae, which provide us with more information about the body structure in this order of insects.